Work engagement, a scientific conception: interview to Wilmar Schaufeli - Juárez-García, Arturo (2015)
Wilmar Schaufeli is a professor of work psychology and organizations at the University of Utrecht in the Netherlands and a distinguished professor at the University of Leuven in Belgium. He was listed as the most productive professor by the Dutch journal for psychology and its border areas (1993-1995). In 2010, the European Academy of Occupational Health Psychology distinguished him as a "fellow" for his outstanding career and contributions to the field. It is ranked 22th among the most important academics in the field of administration and is also on the list of "the most influential scientific minds in the world" for its high number of appointments at Thomson Reuters. He is currently recognized for his creation of the modern concept of "Engagement" and for being the author of the "Utrecht Work Engagement Scale (UWES)" scale. This interview was conducted in Mexico by the author of the present (AJ) in 2010 during his hearing as a keynote speaker at the 3rd congress of psychosocial factors at work organized by the Network of Researchers on Psychosocial Factors of Work in Mexico City.